A study of blood lead level of children from clinics in two districts in Perak, 1997 - Asmah Zainal Abidin; Jamal Hisham Hashim (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study has been conducted among 238 children from two study areas selected, namely the Trong Clinic in Taiping (rural area) and the Kampong Simee Clinic in lpoh ( urban area). The main objective of the study is to assess the blood lead level and the effect of lead exposure on the health of children aged 1 to 9 years old who have been selected through random sampling. This study also investigated the difference in blood lead level between the two study areas. Blood lead analysis was based on the method by Sinclair and Dohnt. The results showed that the mean blood lead levels of the Trong f children (5.14 µg /dL) was significantly higher compared to the children in Kampong Simee (3.89 µg /dl). The levels of exposure to lead showed that about 3.39% of the children blood samples that was analyzed contained lead above 10 microgram/l00ml. This study showed that blood lead has a significant association with age, study location, nutritional status, behavioral score and health effects score. This study found that the age group between 5 and 6 years old has a higher risk compared to younger age group. Low nutritional status has a significant association with blood lead. High risk behaviors which are significantly associated with blood lead are use of pacifier, drinking outside of house and playing on the floor while the significant health effect is hyperactivity.